Towards a pedagogical foundation for the teaching of law. (2003)
The Right a discipline it inserts in the Social Sciences Whose study should clarify notions like education, integral formation, teaching, didactics, methodology and evaluation. To educate for the WORTHY LIFE, it is a foundation axiológico that gainers in a single face Pedagogy and Right,. The human being is the starting point and thee arrival of the Education in general and in particular, in the Right. The educational of this area, in their educational practice preponderadamente goes to the Masterful Class and it is forged in the classroom of class in an empiric way starting from the imitation of styl observed in its own educational experience as student. To the abilities of Right it corresponds them to be endowed of a technical of a technical body that mates the Pedagogy with the Right.